2015
DOI: 10.1590/abd1806-4841.20153255
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal lichen planus

Abstract: Lichen planus is a chronic inflammatory disease that affects the skin, mucous membranes, nails and scalp. Esophageal lichen planus is a rarely reported manifestation of lichen planus, presenting itself commonly in middle-aged women, with symptoms such as dysphagia. We report a case of esophageal lichen planus in a 54-year-old woman associated with oral, cutaneous and ungual lichen planus. Although lichen planus is a disorder well known by dermatologists, reports of esophageal lichen planus are rare in dermatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
(15 reference statements)
0
19
0
Order By: Relevance
“…Due to its rare nature, there is a paucity of data investigating ELP, and our understanding of the disease is mainly derived from case reports and case series. The most common presenting symptom is dysphagia, though some patients may also experience odynophagia and many are asymptomatic 3 5–8. A review of 72 cases of ELP performed by Fox et al showed that 99% of this cohort had extraoesophageal manifestations of lichen planus, most often oral (89%), vulvovaginal/anogential (42%) and cutaneous (38%) 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its rare nature, there is a paucity of data investigating ELP, and our understanding of the disease is mainly derived from case reports and case series. The most common presenting symptom is dysphagia, though some patients may also experience odynophagia and many are asymptomatic 3 5–8. A review of 72 cases of ELP performed by Fox et al showed that 99% of this cohort had extraoesophageal manifestations of lichen planus, most often oral (89%), vulvovaginal/anogential (42%) and cutaneous (38%) 5.…”
Section: Discussionmentioning
confidence: 99%
“…Data show that the majority of ELP involves the proximal third of the oesophagus 5. Histopathology is very important in making a diagnosis, and the presence of Civatte bodies, necrotic keratinocytes that appear eosinophilic on light microscopy, is confirmatory for ELP 3–8. Direct immunofluorescence can be used if histology is inconclusive 9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preservation of gastroesophageal junction in ELP is an important resource that helps in the differentiation of ELP and gastroesophageal reflux disease. 3 Malignant transformation of ELP to squamous cell carcinoma has been reported in the literature; due to this fact, endoscopic surveillance is recommended. 4,5 Histological findings in the esophagus resemble those from oral mucosa and reflect chronic junctional inflammatory aggression mediated by mature T lymphocytes, which include a band-like lymphocytic infiltrate involving the superficial lamina propria and basal epithelium, besides basal layer degeneration with and apoptotic basal keratinocytes (Civatte bodies).…”
Section: Discussionmentioning
confidence: 99%